Hubungan Kemampuan Membaca Permulaan Dengan Hasil Belajar Siswa Kelas III SDN Panjo - Geyshita Nadya Molawan; Herlina Herlina; Kadek Hariana; Arif Firmansyah; Surahman Surahman (JURNAL DIKDAS, 2025)
This study aimed to determine whether there is a relationship between beginning reading ability and the learning outcomes of third-grade students at SDN Panjo. This research employed a quantitative approach with a correlational research design. The subjects of this study were all 24 third-grade students of SDN Panjo. Data were collected through observation, beginning reading ability tests, and documentation of students’ learning outcomes.The collected data were analyzed using descriptive statistical analysis to describe students’ beginning reading abilities and learning outcomes, as well as inferential statistical analysis to examine the relationship between variables. The inferential analysis used the Spearman Rank correlation technique, as the data were not normally distributed and the sample size was relatively small. Hypothesis testing was conducted at a significance level of 5% (α = 0.05) with a sample size of 24 students. The results of the inferential statistical analysis showed that the calculated correlation coefficient (r_calculated) was greater than the critical value (r_table), namely 0.490 > 0.404. This finding indicates that there is a significant relationship between beginning reading ability (variable X) and students’ learning outcomes (variable Y) of third-grade students at SDN Panjo.